Seeking Safety Group Therapy for Co-Occurring Substance Use Disorder and PTSD among Transgender Women Living with HIV: A Pilot Study. Issue 4 (8th August 2017) - Empson, Susannah; Cuca, Yvette P.; Cocohoba, Jennifer; Dawson-Rose, Carol; Davis, Katy; Machtinger, Edward L.
ABSTRACT: Transgender women living with HIV experience high rates of substance use, violence, and post-traumatic stress disorder (PTSD). Seeking Safety is a manualized, present-focused, cognitive-behavioral therapy program designed to address co-occurring substance use and PTSD. Seeking Safety has evidence of efficacy in a variety of populations but had not been evaluated specifically with people living with HIV or transgender women. We pilot-tested a 12-session Seeking Safety program with a group of transgender women living with HIV who reported substance use and a history of violence. Seven transgender women living with HIV were recruited from two HIV primary care clinics in San Francisco and completed pre- and post-intervention assessments. Participants attended an average of 8 of the 12 sessions. Mean scores for all three outcome measures improved: PTSD symptom scores declined 17.5%, alcoholism screening scores declined 23.9%, and drug abuse screening scores declined 68.8%, on average. Despite the small sample, this pilot study showed Seeking Safety to be a promising intervention among transgender women living with HIV. The findings are encouraging and justify larger studies of Seeking Safety among transgender women and other people living with HIV who experience high rates of substance use and PTSD.